Effect Scoring Method on Oocyte Maturation, Fertilization and Development Embryo Production from Local Buffalo Oocyte.: 1Ihsan A. Habeeb , 2Suhailla O. Hussain and 3Saad M.Al- Sariy - Habeeb, Ihsan A.; Al- Sariy, Saad M. (The Iraqi Journal of Veterinary Medicine, 2019)
The study was conducted to investigate the effect of harvesting methods (Scoring and Aspiration) on maturation oocytes, in vitro fertilization (IVF) and embryo development. This study was conducted at the laboratories of Theriogenology Department of Surgery and Obstetrics, College of Veterinary Medicine Basrah University, during the period extended from December 2018 to the end of March 2019. Samples from female and male reproductive system testis (50 Ovaries and 10 testes) were collected from (Al-Basrah abattoir house) after slaughter at fifteen minutes. All samples were transported in sterilize and clean boxes at (37ºC) within 1-2hrs to the center research unit. Oocytes were collected by Scoring and Aspiration methods. Only grad A and B quality oocytes were selected and incubated in an appropriate maturation medium (TCM-199) at 5% CO2, 38.5 °C and 95% humidity for 24-28 hrs. Spermatozoa were obtained by slicing of caudal epididymal of buffalo's bull. Sperms with matured oocytes were incubated in an appropriate maturation medium at 5% CO2, 38.5°C and 95% humidity from 16 -20 hrs. Fertilized ova was re-incubated in fresh media with changes 50% of media every day and examined every 24hrs for (3) days to follow embryonic development .The results showed: high significant (P<0.05) difference in the mean of collected oocytes in Scoring method than Aspiration method. There was high significant (P<0.05) difference in the percentage of grade A collection oocytes in aspiration method than scoring method. On the other hand the percentage of grade B and C oocytes in Scoring method was high significant (P<0.05) difference than Aspiration method. The percentages of Oocytes maturation in aspiration method was high significant (P<0.05) than scoring method, while the rate of oocyte fertilization was non- significant between two methods. Besides, the percentages of embryos development ( 2, 4 and 8) cells in aspiration method was significant than Scoring method.